If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + -8 = 4(3a + 1) + -3 Reorder the terms: -8 + 2a = 4(3a + 1) + -3 Reorder the terms: -8 + 2a = 4(1 + 3a) + -3 -8 + 2a = (1 * 4 + 3a * 4) + -3 -8 + 2a = (4 + 12a) + -3 Reorder the terms: -8 + 2a = 4 + -3 + 12a Combine like terms: 4 + -3 = 1 -8 + 2a = 1 + 12a Solving -8 + 2a = 1 + 12a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12a' to each side of the equation. -8 + 2a + -12a = 1 + 12a + -12a Combine like terms: 2a + -12a = -10a -8 + -10a = 1 + 12a + -12a Combine like terms: 12a + -12a = 0 -8 + -10a = 1 + 0 -8 + -10a = 1 Add '8' to each side of the equation. -8 + 8 + -10a = 1 + 8 Combine like terms: -8 + 8 = 0 0 + -10a = 1 + 8 -10a = 1 + 8 Combine like terms: 1 + 8 = 9 -10a = 9 Divide each side by '-10'. a = -0.9 Simplifying a = -0.9
| 3x-21=2 | | y^2-3y=10 | | 2y-7=10-7k | | 5x^2-4x+17=0 | | 3(51/10-4)751/10-9= | | 5(8x-7)=37 | | X+3x-5=2 | | 4(3p+2)-10=1 | | %x1200=62000 | | 7-2(2a-3)=9 | | x+1-2x=3 | | 2x-x+3=-44 | | 25n+10n=98 | | (5-7x)-(-8x+9)=(16x+22)-(6x-12) | | 6ln(4x+8)=24 | | t^2+22t+100=0 | | 1.3-5r=-7.4 | | -16r+14r+12=20 | | 2=11+3(m+9) | | 2(x-5)+4z=5-3z | | -v+12v=-11 | | 4(x-2)+x=13 | | -8(-8k-6)=-6 | | 4x+1.50=33.00 | | y^2-8y+16=4 | | x^2-y=-4 | | 7y+3y=12y-2 | | (3x+5)(x^3-4x^2+x-1)= | | 3h-5h+17h-8h=-14 | | 5n+9=2n+1 | | 9x-3+x=7 | | 12+c=-38 |